Determination of Geothermal Fluid Characteristics in Pawan and Pendalian IV Koto Villages, Rokan Hulu Regency, Riau Province Using Geochemical Methods - Rifa Lihayati; Muldarisnur Muldarisnur; Marzuki Marzuki (Jurnal Penelitian Pendidikan IPA, 2022)
Geothermal in Pawan and Pendalian IV Koto Villages is one of the post-volcanic geothermal areas in the Rokan Hulu Regency. This study aims to determine the characteristics of geothermal fluids and estimate reservoir temperature based on geothermometer estimation. The research method used in the study consisted of several stages, namely field data collection and fluid geochemical analysis. The research results from 12 hot springs plotted on the Cl-Li-B triangle diagram show that all hot water samples are dominated by Cl, indicating that the hot springs are far from the geothermal reservoir. The Cl-SO4-HCO3triangle diagram shows that all of the hot springs are bicarbonate water types dominated by HCO3. The Na-K-Mg triangle diagram shows that all fluid samples are in the immature water area, which indicates that the fluid has undergone a reaction with other elements or the influence of meteoric water is quite dominant. The results of calculations with a geothermometer, the estimated reservoir temperature in the geothermal area is in the range of 160.69Â°-176.76Â°C, which is included in the medium-temperature reservoir system. Geothermal in this area can be used as the geothermal potential for developing geothermal power plants.